2020
DOI: 10.1051/matecconf/202031801022
|View full text |Cite
|
Sign up to set email alerts
|

Green Face of Packaging – Sustainability Issues of the Cosmetic Industry Packaging

Abstract: Packaging is a steadily growing industry that faces many challenges as well. Ever growing consumer expectations, though competition, technological advances don’t come even close to the huge issue of sustainability within the industry. Packaging for the beauty industry is dependable on the looks more than any other with massive changes in the recent years since extensive grooming became a part both genders lifestyle today and spreading those standards across the globe. The global cosmetic packaging market was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…According to the European Strategy for plastics in a circular economy introduced by the European Commission, all plastic packaging must be 100% recyclable (or reusable) and 55% should be recycled by 2030 [49]. To make packaging more sustainable, it should have an increased recycling rate, based on the effective amount of plastic waste turned into secondary plastics [46][47][48][49][50]. Another solution in terms of alternative packaging is the use of bio-based materials derived from bamboo, seaweed, corn starch, mushroom fibres, and avocado nuts [51].…”
Section: Packagingmentioning
confidence: 99%
“…According to the European Strategy for plastics in a circular economy introduced by the European Commission, all plastic packaging must be 100% recyclable (or reusable) and 55% should be recycled by 2030 [49]. To make packaging more sustainable, it should have an increased recycling rate, based on the effective amount of plastic waste turned into secondary plastics [46][47][48][49][50]. Another solution in terms of alternative packaging is the use of bio-based materials derived from bamboo, seaweed, corn starch, mushroom fibres, and avocado nuts [51].…”
Section: Packagingmentioning
confidence: 99%
“…According to various formulas applied to manufacture products, soap packaging materials have been engineered to adequately protect soap during distribution, storage, sale, shipping, and use. Paper, waxed papers, aluminum, and, to some extent, a film such as biaxially oriented polypropylene, polyethylene glycol coated paper, low-density polyethylene, cellophane, and other materials have been used as packaging materials ( Drobac et al, 2020 ; Malik et al, 2017 ). The analysis of the municipal solid waste demonstrated that containers and packaging waste accounted for 82.2 million tons of the total waste produced in 2018 ( Anon, 2021b ).…”
Section: Soap Packaging Waste Managementmentioning
confidence: 99%
“…There is also increasing consumer interest in sustainable packaging and plastic-free cosmetics [18][19][20]. Large cosmetics companies have set up impressive goals for packaging [21], and several cases are mentioned in the scientific [22][23][24][25][26][27][28] and trade [20,[29][30][31][32][33][34] literature. Yet, popular brands typically do not offer sustainably packaged color cosmetics, leading to "consumer helplessness in this regard, and a belief that changes should be led by cosmetics producers and government regulatory action" [35].…”
Section: Introductionmentioning
confidence: 99%
“…Globalization helped create large cosmetics multinational corporations (MNCs) which often off-shored production and manufacturing facilities to developing economies [27]. Companies such as L'Oreal acquired Helena Rubenstein, while Unilever acquired Rimmel and Faberge, and Revlon bought Max Factor and Almay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation